Irisin is an Effector Molecule in Exercise Rehabilitation Following Myocardial Infarction (Review) - Qin, Shuguang; Tian, Zhenjun; Boidin, Maxime; Buckley, Benjamin J. R.; Thijssen, Dick H. J.; Lip, Gregory Y. H. (Frontiers in Physiology, 2022)
Background: Regular exercise is an effective non-pharmacological therapy for treatment and prevention of cardiovascular disease (CVD). The therapeutic benefits of exercise are mediated partly through improved vascular and increase in metabolic health. Release of exercise-responsive myokines, including irisin, is associated with beneficial effects of exercise in CVD patients. Observations: The present review provides an overview of the role of exercise in cardiac rehabilitation of patients with myocardial infarction (MI). Further, the role of irisin as a motion-responsive molecule in improving vascular and metabolic health is explored. Possible mechanism of cardioprotective effect of irisin-mediated exercise on myocardial infarction are also summarized in this review. Conclusion and significance of the review: Irisin is associated with reduced inflammation, antioxidant properties, and anti-apoptotic effect, implying that it is a potential key mediator of the beneficial effects of exercise on vascular and metabolic health. The findings show that irisin is a promising therapeutic target for treatment of patients with cardiovascular disease, particularly post-MI. Further research should be conducted to elucidate the potential mechanisms of cardioprotective effects of irisin and explored whether irisin induced by exercise exerts rehabilitation effects post-MI.